THE ROLE OF DONOR INSTITUTIONS IN SUPPORTING THE NON- PROFIT SECTOR IN SAUDI ARABIA, MODEL: SULAIMAN AL RAJHI FOUNDATION. - khadidja, Khaldi; Abdellatif , Habi; Aishah, Alturki (The journal of contemporary issues in business and government, 2024)
Donor institutions play an important role in supporting charitable work in Saudi Arabia, for they sponsor several charity projects. It is considered one of the main components of non- profit sector. About 121 official donors are found throughout the Kingdom with various kinds of support including all voluntary and charitable fields. The most famous and prevalent one is Suliman Al Rajhi Foundation. The purpose of this research is to perceive the performance of donor institutions (Suliman Al Rajhi Foundation as a model), its procedures, policies and stereotypes from the charities’ point of view to help identify weaknesses and strengths of these institutions. This would help these institutions contribute and follow the aspirations and objectives of the Kingdom’s Vision 2030 regarding non-profit sector (which aims to increase its contribution to Domestic Product from 0.3% to 5%.